Primary Leiomyosarcoma of the Ovary: A Case Report of a Rare Ovarian Malignancy - Bangasan, Dixie Jane; Billod, Jimmy (Asian Pacific Journal of Cancer Care, 2025)
Primary leiomyosarcoma of the ovary is a sporadic ovarian tumor constituting less than 0.1% of ovarian malignancies. This ovarian tumor is noted to have a very poor prognosis and generally affects post-menopausal women with few exceptions involving cases seen in younger women, as in the index case. Due to its rarity, there are no large series of case reports in the literature, and definitive treatment guidelines have not yet been developed. This report presents a reproductive woman with primary ovarian leiomyosarcoma who underwent exploratory laparotomy and total hysterectomy with bilateral salpingo-oophorectomy, received adjuvant chemotherapy postoperatively and later underwent tumor debulking post chemotherapy.